NIR‐Laser‐Controlled Hydrogen‐Releasing PdH Nanohydride for Synergistic Hydrogen‐Photothermal Antibacterial and Wound‐Healing Therapies. (7th October 2019) - Yu, Siming; Li, Guowei; Zhao, Penghe; Cheng, Qikun; He, Qianjun; Ma, Dong; Xue, Wei
Abstract: For decades, hydrogen (H2 ) gas has been recognized as an excellent antioxidant molecule that holds promise in treating many diseases like Alzheimer's, stroke, cancer, and so on. For the first time, active hydrogen is demonstrated to be highly efficient in antibacterial, antibiofilm, and wound‐healing applications, in particular when used in combination with the photothermal effect. As a proof of concept, a biocompatible hydrogen‐releasing PdH nanohydride, displaying on‐demand controlled active hydrogen release property under near‐infrared laser irradiation, is fabricated by incorporating H2 into Pd nanocubes. The obtained PdH nanohydride combines both merits of bioactive hydrogen and photothermal effect of Pd, exhibiting excellent in vitro and in vivo antibacterial activities due to its synergistic hydrogen‐photothermal therapeutic effect. Interestingly, combinational hydrogen‐photothermal treatment is also proved to be an excellent therapeutic methodology in healing rats' wound with serious bacterial infection. Moreover, an in‐depth antibacterial mechanism study reveals that two potential pathways are involved in the synergistic hydrogen‐photothermal antibacterial effect. One is to upregulate bacterial metabolism relevant genes like dmpI, narJ, and nark, which subsequently encode more expression of oxidative metabolic enzymes to generate substantial reactive oxygen species to induce DNA damage and another is to cause severe bacterial membrane damage to release intracellular compounds like DNA. Abstract : In this work, active hydrogen is demonstrated to be highly efficient in antibacterial, antibiofilm, and wound‐healing therapies, in particular when used in combination with the photothermal effect. Combinational hydrogen‐photothermal treatment exerts a strong antibacterial effect either by upregulating metabolism‐relevant genes to trigger reactive oxygen species–dependent oxidative stress or causing bacterial membrane damage to release intracellular compounds like DNA.